Study guides

Q: What is the answer to 3x plus 2y - 5 equals 0 x equals y plus 10?

Write your answer...

Submit

Related questions

(2, -1)

-3x + 2y = 9 2y = 3x + 9y = 1,5x + 4,5

(4, -1)

3x + 2y = 7

3x-2y-7=0

3x + 2y = 8 This is an equation. It could be the equation of a line.

3x = 2y + 7 The standard form is: 3x - 2y - 7 = 0

3x+2y=9 2y=9-3x y=-1.5x-4.5

3x+2y=6 2y=-3x+6 y=-1.5x+3

3x+2y = 1 2y = -3x+1 y = -1.5x+0.5

3x plus 2y can be expressed mathematically as (3x + 2y).

Multiply the first equation by -3

3x + 2y = 12 ie 2y = 12 - 3x so y = 6 - 3x/2

-3x + 2y = 12-3x + 3x + 2y = 3x + 122y = 3x + 122y/2 = 3x/2 + 12/2y = (3/2)x + 6

y=2.5 and x=5

4x-2y+3x+2y When simplified: 7x

The equation can be simplified to show a value of Y in terms of X. 3X + 2Y +2 = 4Y + 4 3X + 2 = 2Y + 4 3X -2 = 2Y and 2Y = 3X - 2 means that Y = (3/2 X) -1

(1, 0)

(-2, 4)

(-1, 5)

(-1, 0)

(-1, 5)

3x + 5 + x + 10 + 2y 4x + 2y + 15 |:2 2x + y + 7.5 2x + y + 7.5 is equivalent to the original.

There are 2 unknowns

If: 3x+2y = 5x+2y = 7 Then: 3x+2y = 7 and 5x+2y = 7 Subtract the 1st equation from the 2nd equation: 2x = 0 or x = o By substitution: x = 0 and y = 3.5